Proteolytic theory of pathogenesis of influenza and improvement of its treatment - Divocha, V.A.; Gozhenko, A.I.; Mikhalchuk, V.N. (Актуальні проблеми транспортної медицини, 2011)
A new theory of grippe pathogenesis with the use of proteinase-inhibitory system has been offered. It has been established that purification and concentration of grippe viruses by different methods did not release the virus from the cellular enzymes. When the experimental animals have been infected with grippe virus, we have observed misbalance in enzyme-inhibitory balance took place, especially during first hours after infection. Six isoforms of trypsin-like proteinases were obtained from the lungs of healthy mice. Antiproteinase immune sera have been isolated from these 6 isoforms which served to treat the experimental animals. It was antiserum to the third isoform that has prevented the experimental animals mortality. From the industrial wastes of gamma-globin manufacture the inhibitors of protein-like proteinases have been extracted which prevented the white mice’s mortality in 80% of cases. Endogenous inhibitors of human blood proteinases are prospective in producing anti-influenza drugs for humans.